Kelarutantumpatansementara Cavit dalamrendamansaliva buatan (Solubility of Cavit temporary filling immersed in artificial saliva) - Juni Jekti Nugroho; Hasrul Husain (DiscoverSys Inc., 2014)
A continuous temporary filling inside the mouth would expose acid produced by microorganism during fermentation ofcarbohydrate that would lower the pH of saliva. The aim of this research is to determine the variation on solubilitylevels of Cavit temporary filling immersed in artificial saliva with pH 4, 6, and 8. Samples were placed in tubecontainers with 2 mm in height and 7 mm in diameter. Samples were immersed in four different groups of artificialsaliva based on the pH, in which the first group was immersed in artificial saliva pH 4, the second in pH 6, the third inpH 8, and the fourth group was immersed in distilled water (pH 7). The results showed that after 7 day of immersion,there was a significant difference on solubility levels between the four groups of treatment (p<0.05). The data weretabulated and analyzed using one-way ANOVA and least significant difference (LSD). Therefore, it can be concludedthat pH can affect the solubility levels of Cavit temporary filling.